Biomimetic metalloenzyme taking polyamide derivative as core as well as preparation method and application of biomimetic metalloenzyme
By designing a bionic metallozyme with polyamide derivatives as the core, using the nucleic acid shell to protect the catalytic active center and hydrophobic properties to form an efficient catalytic environment, the problems of stability and catalytic efficiency of bionic metallozyme in cells are solved, and high biosafety is achieved Sexual and targeted high-efficiency intracellular catalysis.
Patent Information
- Application Number
- CN202411242932.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-05
AI Technical Summary
The reduced stability, decreased activity, difficulty in accessing cells, limited catalytic efficiency and cytotoxicity problems caused by metal ions leakage in the cell limit their potential in biocatalytic and medical applications.
Using a bionic metallozyme with polyamide derivatives as the core, through the design of hyperbranched polyamide and polyvalent nucleic acid conjugates, the catalytic activity center is protected by the nucleic acid shell, combined with hydrophobic properties to form an efficient catalytic environment to avoid metal ions leakage. Targeted cell entry is achieved through specific nucleic acid sequences.
High biosafety, low immunogenicity, and targeted high-efficiency intracellular catalysis are achieved, catalytic activity is maintained and the risk of metal ion leakage is reduced, and the biocompatibility and catalytic performance of bionic metal enzymes are improved.
Smart Images

Figure CN119119459A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of biomedicine and relates to a bionic metal enzyme, in particular to a bionic metal enzyme with a polyamide derivative as a core and a preparation method and application thereof. Background Art
[0002] Intracellular catalysis has attracted increasing attention in recent years because it provides a simple and efficient way to directly control biochemical processes or produce molecules of interest in cells. To obtain enhanced functionality and realize the usefulness of catalysis in cells, it would be desirable to expand the scope of “catalyzable” reactions using these intracellular catalysts to achieve more abiotic transformations. However, most metal complexes with catalytic properties show reduced activity or even complete inactivation under biologically relevant conditions because the coordinated biomolecules are poisoned in such environments. One widely adopted solution is to introduce artificial scaffolds, such as single-chain nanoparticles (SCNPs), dense shell nanoparticles (DSNPs), proteins, and inorganic nanomaterials, for those catalytic metal complexes. These intracellular catalytic strategies have successfully brought more catalytic species into cells; but accompanying problems such as cytotoxicity, low cellular uptake, difficult metal scaffold assembly, and limited protection effects of metal centers still often hinder their application.
[0003] Intracellular biomimetic metalloenzymes show great potential in biocatalysis and medical applications, but they still face multiple challenges in practical applications. The inventors of this application previously explored the possibility of intracellular catalysis of SNAs, but the catalytic effect was not ideal in animal models (Molecularly pure miktoarm spherical nucleic acids: preparation and usage as a scaffold for abiotic intracellular catalysis); the inventors further summarized their experience and found that the following problems still exist in biomimetic metalloenzymes:
[0004] First, the complex biological environment inside the cell has a significant impact on the stability of the bionic metal enzyme, causing it to become inactivated. In particular, metal ions may be interfered with by other competing ligands inside the cell, resulting in decreased enzyme activity or inactivation.
[0005] Second: Intracellular biomimetic metal enzymes need to overcome the barrier of biological membranes when entering the cell.
[0006] Third: The catalytic efficiency of intracellular bionic metalloenzymes is often limited in complex biological systems.
[0007] Fourth: The potential toxicity of metal ions in biomimetic metalloenzymes to cells is also a key consideration. If free heavy metal ions are excessive or overactive in cells, they may cause cytotoxic reactions, including oxidative stress, protein dysfunction, and membrane damage.
[0008] Fifth: The immunogenic reaction that may be caused by long-term exposure is also a key point that needs attention. Summary of the invention
[0009] In order to solve the above technical problems, the present invention provides a bionic metal enzyme with a polyamide derivative as the core, and a preparation method and application thereof.
[0010] The technical solution of the present invention is achieved in this way:
[0011] A method for preparing a bionic metal enzyme with a polyamide derivative as a core, comprising the following steps:
[0012] (1) Synthesis of Alkyl-PAMAM Core
[0013]
[0014] Using propiolic acid as a raw material, in a solvent of dichloromethane or DMF, hydroxysuccinimide is used to activate the carboxyl group under the catalysis of triethylamine and dicyclohexylcarbodiimide to obtain an activated ester of succinimide (compound 1), wherein the equivalent ratio of propiolic acid, hydroxysuccinimide, dicyclohexylcarbodiimide and triethylamine is 1:1:1.5:1.5; then an excess of compound 1 (100 equiv.) is used to react with a third-generation PAMAM-NH 2 (1.0 equiv.) was reacted in an ultra-dry methanol system or an ultra-dry ethanol system for 3 to 7 days under the catalysis of triethylamine to obtain a terminal alkyne-modified hyperbranched polyamide derivative Alkyl-PAMAM (compound 2) as a core molecule.
[0015] PAMAM-NH 2 The CAS number is 153891-46-4.
[0016] The structure of Alkyl-PAMAM is:
[0017]
[0018] (2) Synthesis of PAMAM-SNA
[0019]
[0020] Weigh 19.8-90.2 mg of compound 2 (5-21 μmol, 1.0 equiv.) and dissolve it in 5-10 mL of DMF, then add it to a 25 mL round-bottom flask with a magnetic rod. Dissolve 108.8-456.2 mg (31-130 μmol, 6.2 equiv.) of azido-tris (triazole, azido-TTA) in 2-5 mL of DMF, and add it to the above system after it is completely dissolved, passing Ar gas. Weigh 5.85-24.6 mg (32.5-136.5 μmol, 6.5 equiv.) of anhydrous CuSO 4 and 17.0-72.4 mg (32.5-136.5 μmol, 6.5 equiv.) of TBTA ligand (Cas No.: 510758-28-8) were mixed and dissolved in 1-5 mL of DMF. After mixing, the mixture was allowed to stand for 5 min, and then the solution was poured into a flask system protected by Ar atmosphere and stirred at room temperature for two days. After two days, N 3 -DNA chain (the amount of DNA loaded is 77.5-325.5 μmol, 15.5 equiv.) of CPG glass beads. Weigh 10.4-43.5 mg (57.5-241.5 μmol, 11.5 equiv.) of anhydrous CuSO 4 Mix and dissolve 30.5-128.1 mg (11.5 equiv.) of TBTA ligand in 2-10 mL of DMF, let stand for 5 min after mixing, and then inject into the above reaction system. The system maintains an argon protective atmosphere and reacts at room temperature with high-speed stirring for 7 days. After the reaction is completed, the reaction system is filtered to retain the filter residue (CPG glass beads), and the CPG glass beads are rinsed with acetonitrile 5-7 times under suction filtration, and the liquid is drained and blown dry with nitrogen.
[0021] Where: N 3 -The sequence of the DNA chain is shown in SEQ ID No.1:
[0022] 5'-N 3 -TTTTTTTTTTTTTTTTTTGGGTGGTGGTGGTTGTGGTGGTGGTGGT-3'.
[0023] (3) Purification of PAMAM-SNA
[0024] The CPG glass beads obtained in step (2) are placed in a brown sample bottle, and 1-5 mL of ammonia water is added, and the bottle is sealed with a cap and placed at room temperature for 24 hours. The excess ammonia is then blown away with nitrogen, and the mixture of the unreacted DNA and fragments cut off and the SNA target product is separated and purified by RP-HPLC to obtain pure SNA. The solution is then freeze-dried to obtain SNA freeze-dried powder, which can be stored for a long time (>2 years) at -20°C.
[0025] The bionic metalloenzyme prepared in the present application has the following general structural formula:
[0026]
[0027] Where:
[0028] R is a complex of TBTA, and its structural formula is: N 3 -DNA strand: 5'-N 3 -TTTTTTTTTTTTTTTTTTGGGTGGTGGTGGTTGTGGTGGTGGTGGT-3'.
[0029] The application of the above-mentioned bionic metal enzyme in the preparation of intracellular catalysts.
[0030] The application of the above-mentioned bionic metal enzyme in the preparation of reagents for catalyzing click reactions.
[0031] The present invention has the following beneficial effects:
[0032] 1. The present application prepares a nucleic acid-polyamide polymer catalyst with a core-shell structure that is targeted, highly biosafe, and low immunogenic. In this system, the catalytic active center is protected by the dense outer nucleic acid shell, and at the same time, the molecular structure and hydrophobic properties of the hyperbranched polymer polyamide are used to create a highly "pure" catalytic environment inside, avoiding the dilemma of bionic enzyme inactivation in a complex system, and also avoiding the hidden danger of metal ion leakage in the body. By utilizing the three-dimensional structure of the material, it can enter the cell autonomously through recognition, avoiding the use of highly toxic cationic transfection agents. Some of the more major problems currently faced by bionic metal enzymes are solved.
[0033] 2. The biomimetic metal enzyme of the present application has a three-dimensional structure of a multivalent nucleic acid conjugate that can wrap the catalytic active center well inside the material to ensure its catalytic activity in a complex environment; the multivalent nucleic acid of a specific sequence is modified on the outer layer of the material as a dense shell to form a spherical nucleic acid nanostructure with a special three-dimensional structure. Both polyamide and nucleic acid materials have high biocompatibility. At the same time, because the outer layer is modified with a dense negatively charged nucleic acid outer layer, the protective effect of the invented material on the copper ions in the inner core is very significant. While maintaining its good catalytic activity in the body, it also solves the risk of metal ion leakage. By utilizing the recognition effect of the outer layer of nucleic acid, it can enter the target cells efficiently and targetedly, and the outer layer of nucleic acid sequence can be customized. Only by replacing the sequence of the nucleic acid chain (J.Am.Chem.Soc.2020,142,31,13350-13355. or Adv.Sci.2024,11,2308924.), it is possible to achieve the purpose of targeting different cells and delivering enzyme-mimicking catalysts to them. The method is simple and reliable;
[0034] 3. The core-shell structure of the present application is used to "bind" the internal metal ions, which greatly improves the biosafety of the material; the main component of the material, the single-stranded nucleic acid, is also a material with extremely high biocompatibility. Therefore, this multivalent nucleic acid conjugate with a polyamide derivative as the core can efficiently catalyze the click reaction in the complex biochemical environment in the body, and is an intracellular biomimetic metal enzyme with development potential. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0036] Figure 1 MALDI-ToF mass spectrum of the 16-arm polyamide alkyne derivative core.
[0037] Figure 2 HPLC curves and agarose gel images of PAMAM-SNA and DNA; the left picture is the HPLC curves of PAMAM-SNA (SNA) (red) and DNA raw material (black), and the right picture is the agarose gel images of the two.
[0038] Figure 3 MALDI-ToF mass spectrum of PAMAM-SNA (SNA).
[0039] Figure 4Schematic diagram of the PAMAM-SNA (SNA) structure (in order to show the inner core clearly, the size ratio of the DNA single chain to the inner core is not the actual ratio).
[0040] Figure 5 AFM characterization of PAMAM-SNA (SNA).
[0041] Figure 6 DLS characterization of PAMAM-SNA (SNA) in 0.5 M PBS.
[0042] Figure 7 Cell uptake experiment of Cy3-modified PAMAM-SNA, using MCF7 cells; scale bar: 20 μm.
[0043] Figure 8 The intracellular biocompatibility of PAMAM-SNA catalyst (the cell line is HL7702 cells).
[0044] Fig. 9 Toxicity test of PAMAM-SNA in living zebrafish.
[0045] Fig.10 Nuclease stability test of DNA and PAMAM-SNA.
[0046] Fig.11 This is the catalytic experiment of TBTA and PAMAM-SNA in PBS.
[0047] Fig.12 For catalytic experiments in DMEM medium containing FBS.
[0048] Fig.13 This is the reaction mechanism of PAMAM-SNA and sodium ascorbate.
[0049] Fig.14 This is the intracellular catalytic experiment of PAMAM-SNA (the cell line is MCF-7). DETAILED DESCRIPTION
[0050] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0051] Unless otherwise specified, the experimental methods used in the following experimental examples are all conventional methods; the materials and reagents used are reagents and materials that can be obtained from commercial channels unless otherwise specified.
[0052] The nucleic acid chain N used in this application 3 The sequence of the DNA strand is shown in SEQ ID No. 1 (provided by Sangon Biotech (Shanghai) Co., Ltd.):
[0053] 5'-N 3 -TTTTTTTTTTTTTTTTTTGGGTGGTGGTGGTTGTGGTGGTGGTGGT-3'.
[0054] Example 1
[0055] A method for preparing a bionic metal enzyme with a polyamide derivative as a core, comprising the following steps:
[0056] (1) Synthesis of Alkyl-PAMAM Core
[0057]
[0058] Using propiolic acid as a raw material, in a solvent of dichloromethane or DMF, hydroxysuccinimide is used to activate the carboxyl group under the catalysis of triethylamine and dicyclohexylcarbodiimide to obtain an activated ester of succinimide (compound 1), wherein the equivalent ratio of propiolic acid, hydroxysuccinimide, dicyclohexylcarbodiimide and triethylamine is 1:1:1.5:1.5; then an excess of compound 1 (100 equiv.) is used with a third-generation PAMAM-NH 2 (1.0 equiv.) was reacted in an ultra-dry methanol system for 3 to 7 days under the catalysis of triethylamine to obtain a terminal alkyne-modified hyperbranched polyamide derivative Alkyl-PAMAM (compound 2) as the core molecule.
[0059] PAMAM-NH 2 The CAS number is 153891-46-4.
[0060] The structure of Alkyl-PAMAM is:
[0061]
[0062] (2) Synthesis of PAMAM-SNA
[0063]
[0064] Weigh 19.8-90.2 mg of compound 2 (5 μmol, 1.0 equiv.) and dissolve it in 5-10 mL of DMF, then add it to a 25 mL round-bottom flask with a magnetic rod. Dissolve 108.8-456.2 mg (31 μmol, 6.2 equiv.) of azido-tris (triazole, azido-TTA) in 2-5 mL of DMF, and add it to the above system after it is completely dissolved, passing Ar gas. Weigh 5.85 mg (32.5 μmol, 6.5 equiv.) of anhydrous CuSO 4 and 17.0 mg (32.5 μmol, 6.5 equiv.) of TBTA ligand (Cas No.: 510758-28-8) were mixed and dissolved in 1-5 mL of DMF. After mixing, the mixture was allowed to stand for 5 min, and then the solution was poured into a flask system protected by Ar atmosphere and stirred at room temperature for two days. After two days, N 3 -DNA chain (the amount of DNA loaded is 77.5 μmol, 15.5 equiv.) of CPG glass beads. Weigh 10.4 mg (57.5 μmol, 11.5 equiv.) of anhydrous CuSO 4 Mix and dissolve 30.5 mg (11.5 equiv.) of TBTA ligand in 2 mL of DMF, let stand for 5 min after mixing, and then inject into the above reaction system. The system maintains an argon protective atmosphere and reacts at room temperature with high-speed stirring for 7 days. After the reaction is completed, the reaction system is filtered to retain the filter residue (CPG glass beads), and the CPG glass beads are rinsed with acetonitrile 5-7 times under suction filtration, and the liquid is drained and blown dry with nitrogen.
[0065] (3) Purification of PAMAM-SNA
[0066] The CPG glass beads obtained in step (2) were placed in a brown sample bottle, and 1 mL of ammonia water was added, and the bottle was sealed with a cap and placed at room temperature for 24 hours. The excess ammonia was then blown away with nitrogen, and the excised DNA and PAMAM-SNA mixture were separated and purified by HPLC to obtain pure PAMAM-SNA. The solution was then freeze-dried to obtain PAMAM-SNA freeze-dried powder (abbreviated as SNA), which can be stored for a long time (>2 years) at -20°C.
[0067] Maldi-ToF mass spectrometry was performed on the Alkyl-PAMAM core and PAMAM-SNA prepared in this example:
[0068] The chemical structure and time-of-flight mass spectrometry characterization of the Alkyl-PAMAM core are as follows Figure 1As shown: According to the software, the calculated value of the core molecular weight is 4310.4585, and the measured value is 4333.4483, which is the mass of one molecule of sodium ion. The tested mass is highly consistent with the predicted mass, proving the successful synthesis of the core material polyamide alkynyl derivative.
[0069] The theoretical calculated molecular weight of PAMAM-SNA is 157215.8947Da (~157.22kDa), and the measured value is close to the theoretical value. At the same time, since the material is a multivalent nucleic acid conjugate, it can carry multiple charges. The mass-to-charge ratio of the material with 2 and 3 charges can also be observed in the figure, which is about ~78.61kDa and ~52.44kDa, respectively. The test results are highly consistent with the theoretical calculated value. It is inferred that the structural schematic diagram of the PAMAM-SNA material in the present invention is as follows Figure 4 shown.
[0070] For the N used in this embodiment 3 -HPLC and agarose gel characterization of DNA strand raw material and PAMAM-SNA (SNA):
[0071] like Figure 2 As shown, the left picture is raw material N 3 -DNA (black curve) and product SNA (red curve) HPLC curves. Since SNA is a multivalent nucleic acid, its hydrophilicity is enhanced, and the retention time on HPLC is shortened. The right figure is the agarose gel electrophoresis characterization of the two materials. Through the gel electrophoresis experiment, it can be seen that due to the increased size of SNA, the migration rate on the gel is slower than that of the DNA raw material, so the distance to the upper gel hole is closer.
[0072] Dry particle size of PAMAM-SNA (characterized by AFM)
[0073] Through AFM test, such as Figure 5 As shown: it can be seen that the flat size of the material in the dry state is about 30-40nm (due to the collapse of nucleic acids in the vertical direction, the flat particle size of the material is larger to a certain extent); in the vertical direction, since the outer layer of DNA is a flexible chain, it will collapse to a greater extent in the dry state, so the dry height of SNA is measured to be 1.5-2.5nm, which is basically the particle size of the inner core.
[0074] Dynamic hydration particle size of PAMAM-SNA in aqueous solution (DLS characterization)
[0075] The dynamic hydration particle size test (DLS) experiment of SNA in 0.5M PBS, such as Figure 6It can be seen from the figure that the dynamic hydration particle size of SNA in a higher concentration salt solution is 60-80nm, and the distribution width is narrow, which means that the SNA material is still well dispersed in the high concentration salt solution, basically in a dispersed state, and the size is relatively uniform.
[0076] Further, the raw materials and reaction conditions in this example were adjusted, and it was found that the same product as in Example 1 could still be prepared. The adjusted data are shown in Examples 2-5:
[0077] Example 2
[0078] A method for preparing a bionic metal enzyme with a polyamide derivative as a core, comprising the following steps:
[0079] (1) Synthesis of Alkyl-PAMAM Core
[0080]
[0081] Using propiolic acid as a raw material, in a solvent of dichloromethane or DMF, hydroxysuccinimide is used to activate the carboxyl group under the catalysis of triethylamine and dicyclohexylcarbodiimide to obtain an activated ester of succinimide (compound 1), wherein the equivalent ratio of propiolic acid, hydroxysuccinimide, dicyclohexylcarbodiimide and triethylamine is 1:1:1.5:1.5; then an excess of compound 1 (100 equiv.) is used with a third-generation PAMAM-NH 2 (1.0 equiv.) was reacted in an ultra-dry ethanol system for 7 days under the catalysis of triethylamine to obtain a terminal alkyne-modified hyperbranched polyamide derivative Alkyl-PAMAM (compound 2) as the core molecule.
[0082] PAMAM-NH 2 The CAS number is 153891-46-4.
[0083] The structure of Alkyl-PAMAM is shown in Example 1.
[0084] (2) Synthesis of PAMAM-SNA
[0085]
[0086] Dissolve the weighed compound 2 (21 μmol, 1.0 equiv.) in 10 mL of DMF and add it to a 25 mL round-bottom flask with a magnetic rod. Dissolve (130.2 μmol, 6.2 equiv.) of azido-tris (triazole, azido-TTA) in 5 mL of DMF and add it to the above system after it is completely dissolved. Pass Ar gas. Weigh (136.5 μmol, 6.5 equiv.) of anhydrous CuSO4 and (136.5 μmol, 6.5 equiv.) of TBTA ligand (Cas No.: 510758-28-8) were mixed and dissolved in 5 mL of DMF. After mixing, the mixture was allowed to stand for 5 min, and then the solution was poured into a flask system protected by Ar atmosphere and stirred at room temperature for two days. 3 -DNA chain (the amount of DNA loaded is 325.5 μmol, 15.5 equiv.) of CPG glass beads. Weigh (241.5 μmol, 11.5 equiv.) of anhydrous CuSO 4 and (11.5 equiv.) of TBTA ligand were mixed and dissolved in 10 mL of DMF, allowed to stand for 5 min after mixing, and then injected into the above reaction system. The system was maintained in an argon protective atmosphere and stirred at high speed at room temperature for 7 days. After the reaction was completed, the reaction system was filtered to retain the residue (CPG glass beads), and the CPG glass beads were rinsed with acetonitrile 5-7 times under suction filtration, and the liquid was drained and blown dry with nitrogen.
[0087] Where: N 3 The sequence of the -DNA chain is shown in SEQ ID No.1.
[0088] (3) Purification of PAMAM-SNA
[0089] The CPG glass beads obtained in step (2) were placed in a brown sample bottle, and 5 mL of ammonia water was added, and the bottle was sealed with a cap and placed at room temperature for 24 hours. The excess ammonia was then blown away with nitrogen, and the excised DNA and PAMAM-SNA mixture were separated and purified by HPLC to obtain pure PAMAM-SNA. The solution was then freeze-dried to obtain PAMAM-SNA freeze-dried powder, which can be stored for a long time (>2 years) at -20°C.
[0090] Example 3
[0091] A method for preparing a bionic metal enzyme with a polyamide derivative as a core, comprising the following steps:
[0092] (1) Synthesis of Alkyl-PAMAM Core
[0093]
[0094] Using propiolic acid as a raw material, in a solvent of dichloromethane or DMF, hydroxysuccinimide is used to activate the carboxyl group under the catalysis of triethylamine and dicyclohexylcarbodiimide to obtain an activated ester of succinimide (compound 1); the equivalent ratio of propiolic acid, hydroxysuccinimide, dicyclohexylcarbodiimide and triethylamine is 1:1:1.5:1.5; then an excess of compound 1 (100 equiv.) is used with a third-generation PAMAM-NH2 (1.0 equiv.) was reacted in an ultra-dry methanol system or an ultra-dry ethanol system for 3 to 7 days under the catalysis of triethylamine to obtain a terminal alkyne-modified hyperbranched polyamide derivative Alkyl-PAMAM (compound 2) as a core molecule.
[0095] PAMAM-NH 2 The CAS number is 153891-46-4.
[0096] The structure of Alkyl-PAMAM is shown in Example 1.
[0097] (2) Synthesis of PAMAM-SNA
[0098]
[0099] Dissolve the weighed compound 2 (10 μmol, 1.0 equiv.) in 5-10 mL of DMF and add it to a 25 mL round-bottom flask with a magnetic rod. Dissolve (62 μmol, 6.2 equiv.) of azido-tris (triazole, azido-TTA) in 3 mL of DMF and add it to the above system after it is completely dissolved. Pass Ar gas. Weigh (65 μmol, 6.5 equiv.) of anhydrous CuSO 4 and (65 μmol, 6.5 equiv.) of TBTA ligand (Cas No.: 510758-28-8) were mixed and dissolved in 3 mL of DMF. After mixing, the mixture was allowed to stand for 5 min, and then the solution was poured into a flask system protected by Ar atmosphere and stirred at room temperature for two days. 3 -DNA chain (the amount of DNA loaded is 155 μmol, 15.5 equiv.) of CPG glass beads. Weigh (115 μmol, 11.5 equiv.) of anhydrous CuSO 4 and (115 μmol, 11.5 equiv.) of TBTA ligand were mixed and dissolved in 4 mL of DMF, allowed to stand for 5 min after mixing, and then injected into the above reaction system. The system was maintained in an argon protective atmosphere and stirred at high speed at room temperature for 7 days. After the reaction was completed, the reaction system was filtered to retain the residue (CPG glass beads), and the CPG glass beads were rinsed with acetonitrile 5-7 times under suction filtration, and the liquid was drained and blown dry with nitrogen.
[0100] Where: N 3 The sequence of the -DNA chain is shown in SEQ ID No.1.
[0101] (3) Purification of PAMAM-SNA
[0102] The CPG glass beads obtained in step (2) were placed in a brown sample bottle, and 3 mL of ammonia water was added, and the bottle was sealed with a cap and placed at room temperature for 24 hours. The excess ammonia was then blown away with nitrogen, and the excised DNA and PAMAM-SNA mixture were separated and purified by HPLC to obtain pure PAMAM-SNA. The solution was then freeze-dried to obtain PAMAM-SNA freeze-dried powder, which can be stored for a long time (>2 years) at -20°C.
[0103] Example 4
[0104] A method for preparing a bionic metal enzyme with a polyamide derivative as a core, comprising the following steps:
[0105] (1) Synthesis of Alkyl-PAMAM Core
[0106]
[0107] Using propiolic acid as a raw material, in a solvent of dichloromethane or DMF, hydroxysuccinimide is used to activate the carboxyl group under the catalysis of triethylamine and dicyclohexylcarbodiimide to obtain an activated ester of succinimide (compound 1), wherein the equivalent ratio of propiolic acid, hydroxysuccinimide, dicyclohexylcarbodiimide and triethylamine is 1:1:1.5:1.5; then an excess of compound 1 (100 equiv.) is used to react with a third-generation PAMAM-NH 2 (1.0 equiv.) was reacted in an ultra-dry methanol system or an ultra-dry ethanol system for 7 days under the catalysis of triethylamine to obtain a terminal alkyne-modified hyperbranched polyamide derivative Alkyl-PAMAM (compound 2) as the core molecule.
[0108] PAMAM-NH 2 The CAS number is 153891-46-4.
[0109] The structure of Alkyl-PAMAM is shown in Example 1.
[0110] (2) Synthesis of PAMAM-SNA
[0111]
[0112] Dissolve the weighed compound 2 (15 μmol, 1.0 equiv.) in 8 mL of DMF and add it to a 25 mL round-bottom flask with a magnetic rod. Dissolve (93 μmol, 6.2 equiv.) of azido-tris (triazole, azido-TTA) in 4 mL of DMF and add it to the above system after it is completely dissolved. Pass Ar gas. Weigh (97.5 μmol, 6.5 equiv.) of anhydrous CuSO 4and (97.5 μmol, 6.5 equiv.) of TBTA ligand (Cas No.: 510758-28-8) were mixed and dissolved in 4 mL of DMF. After mixing, the mixture was allowed to stand for 5 min, and then the solution was poured into a flask system protected by Ar atmosphere and stirred at room temperature for two days. 3 -DNA chain (the amount of DNA loaded is 232.5 μmol, 15.5 equiv.) of CPG glass beads. Weigh (172.5 μmol, 11.5 equiv.) of anhydrous CuSO 4 and (172.5μmol, 11.5equiv.) of TBTA ligand were mixed and dissolved in 8mL of DMF, allowed to stand for 5min after mixing, and then injected into the above reaction system. The system was maintained in an argon protective atmosphere and stirred at high speed at room temperature for 7 days. After the reaction was completed, the reaction system was filtered to retain the residue (CPG glass beads), and the CPG glass beads were rinsed with acetonitrile 6 times under suction filtration, and the liquid was drained and blown dry with nitrogen.
[0113] Where: N 3 The sequence of the -DNA chain is shown in SEQ ID No.1.
[0114] (3) Purification of PAMAM-SNA
[0115] The CPG glass beads obtained in step (2) are placed in a brown sample bottle, and 1-5 mL of ammonia water is added, and the bottle is sealed with a cap and placed at room temperature for 24 hours. The excess ammonia is then blown away with nitrogen, and the excised DNA and PAMAM-SNA mixture are separated and purified by HPLC to obtain pure PAMAM-SNA. The solution is then freeze-dried to obtain PAMAM-SNA freeze-dried powder, which can be stored for a long time (>2 years) at -20°C.
[0116] Example 5
[0117] A method for preparing a bionic metal enzyme with a polyamide derivative as a core, comprising the following steps:
[0118] (1) Synthesis of Alkyl-PAMAM Core
[0119]
[0120] Using propiolic acid as a raw material, in a solvent of dichloromethane or DMF, hydroxysuccinimide is used to activate the carboxyl group under the catalysis of triethylamine and dicyclohexylcarbodiimide to obtain an activated ester of succinimide (compound 1), wherein the equivalent ratio of propiolic acid, hydroxysuccinimide, dicyclohexylcarbodiimide and triethylamine is 1:1:1.5:1.5; then an excess of compound 1 (100 equiv.) is used to react with a third-generation PAMAM-NH2 (1.0 equiv.) was reacted in an ultra-dry methanol system or an ultra-dry ethanol system for 6 days under the catalysis of triethylamine to obtain a terminal alkyne-modified hyperbranched polyamide derivative Alkyl-PAMAM (compound 2) as the core molecule.
[0121] PAMAM-NH 2 The CAS number is 153891-46-4.
[0122] The structure of Alkyl-PAMAM is shown in Example 1.
[0123] (2) Synthesis of PAMAM-SNA
[0124]
[0125] Weigh 19.8-90.2 mg of compound 2 (8 μmol, 1.0 equiv.) and dissolve it in 6 mL of DMF, then add it to a 25 mL round-bottom flask with a magnetic rod. Dissolve (49.6 μmol, 6.2 equiv.) of azido-tris (triazole, azido-TTA) in 3 mL of DMF, add it to the above system after it is completely dissolved, and pass Ar gas. Weigh (52 μmol, 6.5 equiv.) of anhydrous CuSO 4 and (52 μmol, 6.5 equiv.) of TBTA ligand (Cas No.: 510758-28-8) were mixed and dissolved in 2 mL of DMF. After mixing, the mixture was allowed to stand for 5 min, and then the solution was poured into a flask system protected by Ar atmosphere and stirred at room temperature for two days. 3 -DNA chain (DNA loading amount is 124μmol, 15.5equiv.) CPG glass beads. (92μmol, 11.5equiv.) anhydrous CuSO 4 and (92μmol, 11.5equiv.) of TBTA ligand were mixed and dissolved in 2-10mL of DMF, allowed to stand for 5min after mixing, and then injected into the above reaction system. The system was maintained in an argon protective atmosphere and stirred at high speed at room temperature for 7 days. After the reaction was completed, the reaction system was filtered to leave the residue (CPG glass beads), and the CPG glass beads were rinsed with acetonitrile 6 times under suction filtration, and the liquid was drained and blown dry with nitrogen.
[0126] Where: N 3 The sequence of the -DNA chain is shown in SEQ ID No.1.
[0127] (3) Purification of PAMAM-SNA
[0128] The CPG glass beads obtained in step (2) were placed in a brown sample bottle, and 4 mL of ammonia water was added and the bottle was sealed with a cap and placed at room temperature for 24 hours. The excess ammonia was then blown away with nitrogen gas, and the excised DNA and PAMAM-SNA mixture were separated and purified by HPLC to obtain pure PAMAM-SNA. The solution was then freeze-dried to obtain PAMAM-SNA freeze-dried powder, which can be stored for a long time (>2 years) at -20°C.
[0129] Implementation effect example
[0130] 1. Cellular uptake experiment of PAMAM-SNA (characterization by confocal microscopy)
[0131] Cy3-PAMAM-SNA was prepared by using Cy3-labeled nucleic acid chains for cell uptake experiments. 3 -DNA-Cy3 is:
[0132] 5'-N 3 -TTTTTTTTTTTTTTTTTTGGGTGGTGGTGGTTGTGGTGGTGGTGGT-Cy3-3';
[0133] The preparation steps of Cy3-PAMAM-SNA are as follows: Weigh compound 2 (15 μmol, 1.0 equiv.) and dissolve it in 8 mL of DMF, and add it to a 25 mL round-bottom flask with a magnetic rod. Dissolve (93 μmol, 6.2 equiv.) of azido-tris (triazole, azido-TTA) in 4 mL of DMF, and add it to the above system after it is completely dissolved, and pass Ar gas. Weigh (97.5 μmol, 6.5 equiv.) of anhydrous CuSO 4 and (97.5 μmol, 6.5 equiv.) of TBTA ligand (CasNo.: 510758-28-8) were mixed and dissolved in 4 mL of DMF. After mixing, the mixture was allowed to stand for 5 min, and then the solution was poured into a flask system protected by Ar atmosphere and stirred at room temperature for two days. 3 -DNA-Cy3 chain (the amount of DNA loaded is 232.5μmol, 15.5equiv.) CPG glass beads. Weigh (172.5μmol, 11.5equiv.) of anhydrous CuSO 4and (172.5μmol, 11.5equiv.) of TBTA ligand were mixed and dissolved in 8mL of DMF, allowed to stand for 5min after mixing, and then injected into the above reaction system. The system maintained an argon protective atmosphere and reacted at room temperature with high-speed stirring for 7 days. After the reaction was completed, the reaction system was filtered to retain the residue (CPG glass beads), and the CPG glass beads were rinsed with acetonitrile 6 times under suction filtration. After the liquid was drained, it was blown dry with nitrogen to obtain Cy3-PAMAM-SNA.
[0134] The prepared Cy3-PAMAM-SNA was subjected to a cell uptake experiment. According to the experimental results Figure 7 It can be seen that Cy3-PAMAM-SNA has a very high cell uptake efficiency and can enter cells efficiently without the assistance of a transfection agent.
[0135] 2. Biocompatibility test of PAMAM-SNA
[0136] The test steps refer to Chem.Sci., 2021, 12, 15843-15848. The cytotoxicity of PAMAM-SNA was evaluated using the classic MTT cytotoxicity assay. RAW264.7 cells were treated with DMEM containing PAMAM-SNA in a range of 0.625 to 5 μM (final concentration) and further incubated for 24 hours. Cells without SNA were used as controls. After incubation, the culture medium was removed and the cells were washed with PBS, and then the cell culture medium was replaced with 120 μL of fresh MTT solution (0.5 mg / mL in DMEM) and incubated for another 1.5 hours. The culture medium was replaced with DMSO (100 μL) and the absorbance of the solution at 595 nm was measured with a microplate reader, and the cell viability was calculated by comparison.
[0137] According to the biocompatibility test results Figure 8 It can be seen that the biocompatibility of PAMAM-SNA is very excellent. When the concentration is 10 times higher than the working concentration (0.5 μM), the survival rate of normal somatic cells still reaches more than 95%, indicating that the material has high biosafety.
[0138] 3. Toxicity test of PAMAM-SNA in living zebrafish
[0139] The test experiment refers to Chem.Sci., 2021, 12, 15843-15848, and CuSO 4 The concentration was measured by flow cytometry. The injection concentrations were 20 nM PAMAM-SNA + 120 nM copper sulfate, 120 nM TBTA catalyst + 120 nM copper sulfate, 120 μM azidotriazole ligand + 120 nM copper sulfate, and 120 nM copper sulfate. The four groups of solutions were injected into the zebrafish through the abdominal cavity with an injection volume of 2 μL per fish, and the survival of the zebrafish was observed.
[0140] The results are as follows Fig. 9 As shown, it can be seen from the survival curve that compared with the traditional TBTA ligand chelated copper catalyst or the copper ion catalyst without added ligand, the PAMAM-SNA catalyst has a better survival curve, indicating that it is safer for living organisms.
[0141] IV. PAMAM-SNA and its anti-enzymatic stability test
[0142] The test procedure was to perform digestion experiments of SNA materials and ssDNA under the conditions recommended by the manufacturer. The digestion process was monitored by RP-HPLC using rhodamine dye as an internal standard. The degree of digestion was calculated using the normalized integral values of the corresponding materials at different time points. The HPLC conditions used were: 0.05M TEAA / ACN, from 0.95 / 0.05 to 0.05 / 0.95 in 50 minutes, volume ratio, and a flow rate of 1 mL / min.
[0143] Stability test data Fig.10 It can be seen that PAMAM-SNA material has higher stability and resistance to enzyme cleavage than free DNA.
[0144] 5. In vitro catalytic experiment of PAMAM-SNA
[0145] The test steps refer to Chem. Sci., 2021, 12, 15843-15848. The specific steps are as follows: (1) PBS buffer system: CuSO 4 Concentrator, add 5 μL containing 1 μM PAMAM-SNA and 5 μM CuSO 4 5 μL of catalyst solution containing 5 μM TBTA catalyst and 5 μM CuSO 4 The two groups of solutions were added to 500 μL of 1× PBS solution containing two catalytic substrates, namely 20 μM 3-hydroxy-7-azidocoumarin and 20 μM p-methylphenylacetylene. The fluorescence change of the system was measured by a fluorescence spectrophotometer to obtain the catalytic yield. (2) Serum-medium system: 5 μL of serum-medium system containing 0.5 μM PAMA-SNA and 3 μM CuSO 4 Catalyst solution I, and 5 μL containing 20 μM TBTA and 20 μM CuSO 4 Catalyst solution II, the two groups of solutions were respectively added into 500 μL of DMEM culture medium containing two catalytic substrates, namely 20 μM 3-hydroxy-7-azidocoumarin and 20 μM p-methylphenylacetylene, the culture medium contained 8% fetal bovine serum, and the fluorescence changes of the system were measured by a fluorescence spectrophotometer to obtain the catalytic yield.
[0146] The PAMAM-SNA catalyst prepared by the present invention was used to conduct an in vitro catalytic experiment to preliminarily verify the catalytic performance of the material. Fig.11 and Fig.12 As shown: Compared with the commercially available catalyst TBTA, in the presence of PBS, it can be seen that both TBTA and PAMAM-SNA have catalytic activity ( Fig.11 When the environment is more complex (i.e., in a culture medium with fetal bovine serum), the catalytic performance of the commercially available catalyst is greatly affected, while the PAMAM-SNA catalyst of the present invention can still exhibit high catalytic performance ( Fig.12 ).
[0147] The reaction catalyzed by the present invention is a click reaction between 3-hydroxy-7-azidocoumarin and p-methylphenylacetylene, and the coumarin derivative after the reaction has fluorescence. Among them, Cu(I) is a highly efficient ligand catalyst obtained by the reaction of PAMAM-SNA, the precursor of the intracellular artificial metalloenzyme prepared by the present invention, with sodium ascorbate. The reaction mechanism is as follows Fig.13 shown.
[0148] VI. Intracellular catalytic experiment of PAMAM-SNA (characterization by confocal microscopy)
[0149] The specific steps of the experiment were to incubate 300,000 RAW 264.7 cells for 16 hours to allow them to attach to the plate, and then the cells were incubated with TBTA 20 μM + CuSO 4 20μM, PAMAM-SNA0.5μM+CuSO 4 3μM and PAMAM-SNA 1μM + CuSO 4 A 6 μM solution of the three mixed catalysts was cultured in an incubator for 6 h, and then two substrates (50 μM) and sodium L-ascorbate (1 mM) were added and cultured in a new DMEM solution for 2 h. After washing three times with PBS, 500 μL of PBS was added to the cells and observed using a confocal microscope.
[0150] Intracellular catalysis results Fig.14 It can be seen that, compared with the commercially available catalyst TBTA, the PAMAM-SNA of the present invention can well achieve the catalysis of the substrate in the target cells (the catalytic product has green fluorescence), and can still maintain catalytic activity at a lower working concentration.
[0151] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a bionic metal enzyme with a polyamide derivative as a core, characterized in that: The steps are: (1) Propiolic acid, hydroxysuccinimide, dicyclohexylcarbodiimide and triethylamine are activated in an organic solvent I to obtain an activated ester of succinimide, i.e., compound 1; compound 1, PAMAM-NH2 and triethylamine are further reacted in an organic solvent II to obtain compound 2, i.e., Alkyl-PAMAM; (2) Dissolve the Alkyl-PAMAM and azidotriazole ligands in step (1) in DMF, add anhydrous CuSO4 and TBTA ligand DMF solution in an inert gas atmosphere, stir and react at room temperature, add CPG glass beads loaded with N3-DNA chains, continue to stir and react at high speed in an inert gas atmosphere, and after the reaction is completed, collect the CPG glass beads by filtration, acetonitrile elution, and nitrogen drying; (3) The CPG glass beads treated in step (2) are placed in a brown bottle, and after adding ammonia water, the bottle is sealed and placed, and then the excess ammonia is blown away with nitrogen gas, and the liquid in the brown bottle is collected and separated and purified by HPLC to obtain a bionic metal enzyme with a polyamide derivative as the core, namely PAMAM-SNA.
2. The method for preparing a biomimetic metal enzyme with a polyamide derivative as a core according to claim 1, characterized in that: In the step (1), the equivalent ratio of propiolic acid, hydroxysuccinimide, dicyclohexylcarbodiimide and triethylamine is 1:1:1.5:1.5; the equivalent ratio of compound 1, PAMAM-NH2 and triethylamine is 80-120:1:20; the organic solvent I is dichloromethane or DMF; and the organic solvent II is ultra-dry methanol or ultra-dry ethanol.
3. The method for preparing a biomimetic metal enzyme with a polyamide derivative as a core according to claim 2, characterized in that: The activation reaction is carried out at a temperature of 0-25°C and for a time of 4-8 hours; the reaction is continued for 3-7 days.
4. The method for preparing a biomimetic metal enzyme with a polyamide derivative as a core according to claim 1, characterized in that: The sequence of the N3-DNA chain in step (2) is shown in SEQ ID No. 1, and the 5' end thereof is connected to an N3-group.
5. The method for preparing a biomimetic metal enzyme with a polyamide derivative as a core according to claim 4, characterized in that: The equivalent ratio of the Alkyl-PAMAM, the azidotriazole ligand, the anhydrous CuSO4 and the N3-DNA chain is 1:6.2:18:18:15.
5.
6. The method for preparing a biomimetic metal enzyme with a polyamide derivative as a core according to claim 5, characterized in that: The stirring time at room temperature is 2-3 days, and the high-speed stirring reaction time is 5-7 days.
7. The method for preparing a biomimetic metal enzyme with a polyamide derivative as a core according to claim 6, characterized in that: The sealing time in step (4) is 24 hours.
8. A bionic metal enzyme prepared by the method according to any one of claims 1 to 7, which has the following general structural formula: Where: R is a complex of TBTA, and its structural formula is: ; It is an N3-DNA chain, the nucleotide sequence of which is shown in SEQ ID No. 1, and N3 is connected to its 5' end.
9. Use of the bionic metalloenzyme according to claim 8 in preparing intracellular catalysts.
10. Use of the bionic metalloenzyme according to claim 8 in preparing a reagent for catalyzing click reaction.
Citation Information
Patent Citations
Amphipathic chitosan derivative and preparation method and application thereof
CN102241790A
Cationic polymer as well as preparation method and application thereof
CN102464801A
Supramolecular elastomer networks containing grafted oligoamide hard components
US20170081455A1
Methods and compositions for determining the sequence of nucleic acid molecules
WO1997027331A2
